From chiefs to landlords : social and economic change in the Western Highlands and Islands, c1493-1820 - Dodgshon, R. A. (Robert A.) (Edinburgh : Edinburgh University Press, 1998)
"This new approach to Highland history before the Clearances draws attention to little-studied yet important economic and social processes within the Highland clan system. Robert A. Dodgshon argues for an integrated approach which considers the problems of traditional Highland society, economy and environment together." "Exploring how the different aspects of the clan system - chiefs and kinsmen, landlords and tenants, farming systems, production strategies and marketing - changed over the 16th, 17th, and 18th centuries, it shows how the character and ideology of clans and chiefdoms are inextricably part of the twin problems of socio-political control and food production."--Jacket.
List of figures and tables -- Preface -- List of abbreviations -- Introduction -- 1. The Western Highlands and islands in context, c. 1493-1820 -- 2. Chiefs, kinsmen and territories -- 3. The nature of the chiefly economy -- 4. Patterns of chiefly display and behavior -- 5. The transformation of chiefs into landlords -- 6. The farming township and the institutional basis of farming -- 7. The township economy -- 8. The farming township: Its strategies and constraints -- 9. The Western Highlands and islands on the eve of the clearances -- Bibliography -- Index.
Includes bibliographical references (pages 249-258) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Highlands (Scotland) -- History; Highlands (Scotland) -- Social conditions; Highlands (Scotland) -- Economic conditions; Land tenure -- Scotland -- Highlands -- History; Highlands (Écosse) -- Histoire; Highlands (Écosse) -- Conditions sociales; Highlands (Écosse) -- Conditions économiques.; HISTORY; HISTORY -- Europe -- Great Britain; Economic history; Land tenure; Social conditions; Scotland -- Highlands; Sociaal-economische geschiedenis; Schotse Hooglanden; Countryside Management; History